Analysis of mathematical critical thinking ability of junior high school students in solving problems on two-variable linear equation system - Manurung, Julian Lois; Hutapea, Nahor Murani; Suanto, Elfis (Jurnal Gantang, 2024)
Critical thinking skills are important for students in the process of learning mathematics. Critical thinking skills in the mathematics learning process can help students better understand the material. This study aims to describe students' critical thinking skills in solving problems on the Two-Variable Linear Equation System material. This type of research is descriptive qualitative. The subjects of the study were 18 students of class VIII MTS Daarun Nahdhah Bangkinang. The data collection instruments used in this study were mathematical critical thinking ability test questions and interview sheets. The test to measure students' critical thinking skills consisted of 4 descriptive questions on the Two-Variable Linear Equation System material. The test results were analyzed according to the indicators of critical thinking skills used in this study: Interpretation, Analysis, Evaluation, and Inference. The results of this study stated that the average value of mathematical critical thinking skills of class VIII students of MTS Daarun Nahdhah Bangkinang was 41.99% in the reasonably critical category. The interpreting indicator is in the low category with an average of 25.78%, the analyzing indicator is in the sufficient category with an average of 54.68%, the evaluating indicator is in the sufficient category with an average of 49.21%, and the inferring indicator is in the low category with an average of 38.28%. Based on the research results above, teachers must get used to giving students non-routine questions in learning, using contextual LKPD, and providing varied learning resources to improve students' critical thinking skills.